A comparative analysis of on behavioral patterns and family functioning among children of alcoholics and non-alcoholics in a tertiary care center, Mysuru - Abhigna Mahathi, R. N. S.; Annigeri, Bindu; Shilpa, D. M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Alcohol dependence in individuals harm the health of that individual and also that of their family members. Children of alcoholics are at high risk for many behavioral problems as they grow up in less functional families. This study aimed to assess and compare the behavioral patterns and family functioning among children of alcoholics (COA) and children of non-alcoholics (CONA) in a tertiary care center, Mysuru. Methods: Using analytical cross-sectional design, 200 children (100 COA and 100 CONA) from a tertiary care center, were evaluated for their behavioral patterns and family functioning. Child behavior checklist (CBCL), family APGAR (adaptation, partnership, growth, affect, and resolve) scale and general health questionnaire 12 (GHQ12) were used. Independent t-test was used to compare the two groups and correlation was seen between GHQ12 and CBCL, APGAR scores respectively. Results: The total CBCL mean score was higher for stating statistically significant relation between parental alcoholism and behavioral patterns. Among COA, 45% had CBCL scores more than clinical cutoff score and 4% of COA were associated with dysfunctional family whereas 17% of CONA had CBCL scores more than clinical cutoff score and none were associated with dysfunctional families showing statistically significant difference. Conclusions: Children from families with alcohol dependent parents are at higher risk of having problematic behaviors, interestingly, there were very few families of COAs with dysfunctionality.